To sources of a socially-ecological reality: the house and Road - M. G. Kurbanov (Юг России: экология, развитие, 2015)
The problem of socio-ecological reality origins is considered. Being formed as an integral system, socio-ecological reality suggests multi-dimentional interaction of society and nature when the former is viewed as a sociomorphic organism expressed in such phenomena as home and road. Home is regarded as a collective image converging a special source for «settled» structuring of socioecological reality, while road converging the latter’s «nomadic» structuring.